Legal Responsibility of Notaries Who Commit Fraud in Competing with Notaries - Dewi Tjandraningsih (The International Journal of Law Review and State Administration, 2023)
This research uses a normative juridical and sociological approach as well as explanatory research. The data sources obtained are primary data, secondary data and tertiary data. Primary data collection techniques are carried out by interviewing various respondents who understand and are involved in it. Data collection techniques involve observing the environment in the field and also in the literature. The research method uses descriptive qualitative data analysis. The research results show that: (1). Notaries who engage in unfair competition by not paying the pembayaran determined by the union violate the Notary's code of ethics and are subject to responsibility, in the form of established ethical sanctions. and regulated in the regulations of the Indonesian Notary Association. (2). Juridical implications for Notaries who commit fraud and ask for the minimum pembayaran stipulated by the Notary, can be sued for breach of contract by the Indonesian Notary Association, by issuing a warning or summons to the Notary concerned